Martinez's celebrate 50th anniversary (Raton Range Raton, New Mexico, 1982)
Newspaper Article on the 50th Anniversary of Mr. and Mrs. Lewis Martinez.
Master list item #: 60
File location is in the Raton File Cabinet
Keywords: Martinez, Lewis E; Martinez, (Mrs.); Martinez, Ernest; Martinez, (Mrs.); Sintas, Stella; Chavez, Johnnie Lee; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Albuquerque, New Mexico; Denver, Colorado; New York